Enhancing employee performace through talent management, perceived organizational support and employee engagament - Muhammad Havis Yusuf; Donard Games; Hendra Lukito (Institute of Computer Science (IOCS), 2023)
PT PLN is an Indonesian state-owned company engaged in the electricity sector which has received a target of assignment to provide 100% electrification ratio in Indonesia and also the company must meet the Quality of Service (TMP) for customers. When this study was conducted, the realization of RE was 98.76% and TMP was still below service standards. Therefore, PT PLN must improve their employee performance to exceed customer expectations.This study aims to analyze the application of Employee Engagement in mediating the relationship between Talent Management and Perceived Organizational Support to Employee Performance. The population is focused on employees of PT PLN West Sumatra Distribution Main Unit with a total of 831 participants. Sampling using the quota sampling method was processed using G-Power Statistics software with a sample of 152 participants. By using the Structural Equation Model (SEM)-PLS, the results were obtained that Employee Engagement does not mediate the relationship between Talent Management and Employee Performance, but Employee Engagement as a mediator of the relationship between Perceived Organizational Support and Employee Performance. This research adds to the knowledge of how companies engaged in energy can provide support to their employees, leading to attachments that ultimately have an impact on employee performance.